Seeking victims’ perspective on remedy: the case of Brasil Verde Farm’s workers - Regiane Cristina de Oliveira (Revista Direito GV)
Abstract The awareness that slavery did not disappear with abolition has brought back discussions about dichotomies and tensions that were left unresolved in the context of the abolition. Remedy for people that were enslaved is among these unresolved issues. Brazil became one of the first countries to recognize the existence of contemporary slavery. However, when workers are rescued by government’s agents from slave labor, remedy measures seem inadequate to guarantee that they will surpass the vulnerabilities that lead them to be exploited in the first place. To understand the challenges preventing the effectiveness of the remedy system, this article relies on the collaboration with workers from Barras (Piauí), that were subjected to slave labor in the Brasil Verde Farm. The workers’ narratives – collected through oral history methodology, during a fieldtrip to Piauí, in March 2016 –, help to overcome the ongoing debate on remedy studies related to the discourse of victims’ “wants and needs”, and reveal that any reparation measure that intend to promote social emancipation has to deal with the absences of the right to participation, security, adequate standards of living, health, adequate housing, education, and also access to land.